2004
DOI: 10.1158/0008-5472.can-04-0434
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Effects of Vascular Endothelial Growth Factor Receptor-2-Blocking Antibody plus Fractionated Radiotherapy on Murine Mammary Tumors

Abstract: Although clinical trials of antiangiogenic strategies have been disappointing when administered as single agents, such approaches can play an important role in cancer treatment when combined with conventional therapies. Previous studies have shown that DC101, an antiangiogenic monoclonal antibody against vascular endothelial growth factor receptor-2, can produce significant growth inhibition in spontaneous and transplanted tumors but can also induce substantial hypoxia. Because DC101 appears to potentiate radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…This observation is consistent with reduced oxygenation in histochemically analyzed tumor sections after treatment with the anti-vascular endothelial growth factor receptor-2 antibody DC101 alone but not in response to combined treatment with irradiation (21). However, our results and the results from Fenton et al are in contradiction to the ''tumor vascular normalization'' concept, which claims that treatment with low doses of angiogenesis inhibitors preferentially targets immature vessels and by that creates a normalization window with improved functionality of the remaining tumor vasculature.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This observation is consistent with reduced oxygenation in histochemically analyzed tumor sections after treatment with the anti-vascular endothelial growth factor receptor-2 antibody DC101 alone but not in response to combined treatment with irradiation (21). However, our results and the results from Fenton et al are in contradiction to the ''tumor vascular normalization'' concept, which claims that treatment with low doses of angiogenesis inhibitors preferentially targets immature vessels and by that creates a normalization window with improved functionality of the remaining tumor vasculature.…”
Section: Discussionsupporting
confidence: 82%
“…The FMISO-PET results showed strong correlation with GLUT-1 immunostaining, which was used as an independent approach to assess allograft hypoxia. Thus, FMISO-PET represents a potent method to analyze tumor oxygenation in experimental and clinical settings, to follow treatment responses, and to investigate potential hazards especially of combined treatment modalities (2,21,24). In conclusion, our study has directly investigated in vivo the effects on tumor oxygenation of an antiangiogenic treatment with PTK787, ionizing radiation, or a combination of PTK787 and ionizing radiation.…”
Section: Discussionmentioning
confidence: 96%
“…3,4 Several preclinical studies have indicated that antiangiogenic treatment may enhance the antitumor effect of radiotherapy without increasing damage to normal tissues. [5][6][7][8] Angiogenesis plays a key role in tumor progression. It was hypothesized that inhibition of angiogenesis would be an effective strategy to treat human cancer, and an active search for angiogenesis inducers and inhibitors began in 1971.…”
mentioning
confidence: 99%
“…This is due to the fact that treatments aimed at the suppression of tumor angiogenesis are now well established to block tumor growth, at least in part, by triggering hypoxiamediated death of cancer cell. [8][9][10][11] Some of the anti-angiogenic drugs, such as Avastin (bevacizumab), an anti-vascular endothelial growth factor function-blocking antibody, are presently being UCC CUA UUU, Beclin 1 siRNA-2: GGA AAU CAC UCG UAU CUG GUU, FADD siRNA-1 CGC CAA CGU UGA CAA GGU AUU, FADDsiRNA-2: GCU GAC CAG UGG AAC GUU AUU, casp-9siRNA-1 CGA GAG ACA UGC AGA UAU GUU, casp-9siRNA-2: GCG ACA UGA UCG AGG AUA UUU. All siRNAs were from Dharmacon.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11] Anti-angiogenic therapy now represents one of the most promising approaches for cancer treatment. 12 Molecular mechanisms that regulate hypoxia-induced apoptosis of normal and cancer cells have recently begun to emerge but the understanding of these mechanisms is far from complete.…”
Section: Introductionmentioning
confidence: 99%